Early Stevens-Johnson Syndrome Mimicking Secondary Syphilis: A Case Report - Astrid, Caroline; Bianti, Marsha; Yoedyanto, Hillary Fungestu; Stradivary, Nabilla Wahyu; Putri, Annisa Eka (Journal of Pakistan Association of Dermatologists, 2023)
Stevens-Johnson syndrome/toxic epidermal necrolysis (SJS/TEN) is a rare life-threatening vesicobullous condition caused by immunologic reactions to several stimuli, usually a reaction to certain medications. A 21-year-old Indonesian male adult came to the emergency department with chief complaints of painful erythematous rashes on his hands and feet, watery eyes, and sore throat. He is also been diagnosed with bipolar disorder and currently still on medication. His rash worsened during initial hospitalization and was given appropriate treatment. Stevens-Johnson syndrome is known to be presented as a systemic mucocutaneous lesions with organ involvement. Syphilis is highly infectious sexually transmitted infection and known as "the great imitator" as it often presents as other chronic dermatoses, leading to a difficult and delayed diagnosis. The skin is involved in 70% of cases, with maculopapular, vesiculobullous, and ulcerative morphologies possible at presentation, making the diagnosis of secondary syphilis challenging given its ability to mimic many other conditions. This case emphasizes the importance of pattern recognition of Stevens-Johnson syndrome, as this is a rare but serious condition.